Chinese herbal medicines for the treatment of depression: a systematic review and network meta-analysis - Dang, Chun; Wang, Qinxuan; Li, Qian; Xiong, Ying; Lu, Yaoheng (Frontiers in Pharmacology, 2024)
Objectives: Amidst rising global burden of depression and the associated challenges with conventional antidepressant therapies, there is a growing interest in exploring the efficacy and safety of alternative treatments. This study uses a Bayesian network meta-analysis to rigorously evaluate the therapeutic potential of Chinese herbal medicines in the treatment of depression, focusing on their comparative efficacy and safety against standard pharmacological interventions.Methods: Five databases (PubMed, Wanfang Data, EMBASE, CNKI, and the Cochrane Library) and grey literature were searched from inception to end of July 2023 to identify studies that assessed the efficacy and safety of Chinese herbal medicines in treating depression. The response rate, Hamilton Depression Scale (HAMD) scores, and rates of adverse events were assessed through both direct and indirect comparisons. Data extraction and risk of bias assessment were meticulously performed. Statistical analysis used Markov chain Monte Carlo methods, with effect size estimates provided as odd ratios and their 95% confidence intervals.Results: A total of 198 RCTs involving 8923 patients were analyzed, assessing 17 Chinese herbal medicines. Surface Under the Cumulative Ranking results indicated that the top three treatments with the best response rate were possibly Guipiwan, Ease Pill, and Chaihu Jia Longgu Muli Decoction; the top three treatments on the reduction of HAMD scores were Chai Hu Shu Gan San, Xingnao Jieyu Decoction, and Xiaoyao Powder; and the top three treatments with the lowest adverse effects rates were Xiaoyao Powder, Alprazolam, and Xingnao Jieyu Decoction. Interestingly, commonly used synthetic drugs such as Fluoxetine, Escitalopram, Amitriptyline, Sertraline, Flupentixol and Melitracen, and Venlafaxine, not only appeared to be less effective than specific Chinese herbal medicines (Gan